INDICATORS OF ECONOMIC EFFICIENCY OF SOUR CHERRY IN DIFFERENT PRODUCTION SYSTEMS - Sredojević, Zorica (Journal on Processing and Energy in Agriculture, 2021)
The subject of this research is the economic results of conventional and organic production of sour cherries in the Republic of Serbia. The aim of the research is to determine the economic efficiency and the possibility of greater representation of organic production, as a system of conservation of natural resources and especially land. A minimum selling price of organic cherries (0.44 €/kg) has been set, at which producers can achieve a gross margin of 2,530 €/ha, as well as in the conditions of conventional production. By selling organic sour cherries at a much better selling price (0.50 €/kg) than the price of sour cherries from conventional production (0.36 €/kg), producers manage to "cover" production costs of 2,840 €/ha and achieve a gross margin of 3,910 €/ha. The gross margin includes the reimbursed lost economic benefit of 1,030 €/ha and a profit of 2,880 €/ha.